Straw Sludge Adsorbent Preparation and Characteristics of Research - LIU Bin; WEI Jin-zhi; LEI Jin-ming; MENG Hui-shan; ZHOU Xue-bo (Journal of Harbin University of Science and Technology)
In order to achieve the purpose of sludge and straw resource utilization, a new type of low cost adsorbent was prepared by high temperature sintering with sludge and straw as raw materials, and it could adsorb dye wastewater. The best preparation conditions were screened by thermogravimetric analysis, mechanical strength measurement and electron microscopy analysis. Then, the adsorption performance of methylene blue dye was studied.Experimental results show that when using the activator KOH, carbonized at 850℃, carbonization time was 1h, straw sludge feed ratio of 1∶4 to optimal conditions. When the concentration of methylene blue solution is 20mg/L and the adsorption time is about 5 hours, the decolorization rate of methylene blue dye is the highest, and the highest decolorization rate is more than 80%. Desorption experiments showed that the desorption rate of the granule adsorbent in the 0.05mol/L HCl solution was as high as 78.6%.